2018
DOI: 10.7717/peerj.5106
|View full text |Cite
|
Sign up to set email alerts
|

Who bears the cost of forest conservation?

Abstract: BackgroundWhile the importance of conserving ecosystems for sustainable development is widely recognized, it is increasingly evident that despite delivering global benefits, conservation often comes at local cost. Protected areas funded by multilateral lenders have explicit commitments to ensure that those negatively affected are adequately compensated. We make the first comparison of the magnitude and distribution of the local costs of a protected area with the magnitude and distribution of the compensation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 73 publications
1
63
0
11
Order By: Relevance
“…Different levels of restrictions on use of forest resources by different types of forest conservation interventions can block, to a various degree, some of the mechanisms through which forests affect nutritional status. These restrictions, for example, include limited access to forest food products and non-food products important for income (Poudyal et al, 2018) and therefore may negatively affect nutritional status. On the other hand, forest conservation interventions can also generate benefits through improved ecosystem services, tourism and infrastructure development (Andam et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Different levels of restrictions on use of forest resources by different types of forest conservation interventions can block, to a various degree, some of the mechanisms through which forests affect nutritional status. These restrictions, for example, include limited access to forest food products and non-food products important for income (Poudyal et al, 2018) and therefore may negatively affect nutritional status. On the other hand, forest conservation interventions can also generate benefits through improved ecosystem services, tourism and infrastructure development (Andam et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In these villages, the closest to the respective PAs, populations rely more strongly on shifting cultivation for subsistence rice production and less on cash crop production, suggesting a lack of alternative non-forest-dependent livelihoods, and potentially a stronger impact of PA restrictions compared to Morafeno and Mahalevona. This was recently found for other conservation interventions in Eastern Madagascar (Rasolofoson et al, 2018), where it was also shown that a proportionally larger burden was borne by poorer populations due to restrictions in access to forest land (Poudyal et al, 2018). Restrictions imposed by the PAs might also have an impact on access to bushmeat for households relying on this source of protein, an issue brought up in one of the FGDs and also found in other African settings (Nguiffo, 2003).…”
Section: Protected Areas and Links To Well-beingmentioning
confidence: 69%
“…Many of these new PAs are largely designed, implemented, and managed by international conservation non-governmental organizations (NGOs). While PAs are showing some success in preventing forest loss in the country (Eklund et al, 2016), forest conservation mostly benefits the global community, with local populations incurring large costs (Neudert et al, 2016;Poudyal et al, 2018). In terms of a more comprehensive perspective on well-being, research revealed that community forest management, and strict conservation measures may have a similar magnitude of influence on local subjective well-being, although they may have different effects on individual well-being domains such as livelihood activities or health (Rasolofoson et al, 2018).…”
Section: Introduction: Agricultural Intensification and Human Well-bementioning
confidence: 99%
“…Imposing strict conservation to protect large swathes of the forest has had clear successes over the last decades in the Amazon-about 50% of the Amazon forest is under some kind of protection. However, that in itself does not guarantee protection forever for tropical forests and eventually may affect the livelihoods of local population as is the case documented for Madagascar [69] who may bear a high cost for forest conservation.…”
Section: Discussion and Conclusion: Envisioning The Future For The Amentioning
confidence: 99%